Community Health Promotion Program (PKMRS) Self Care Management Of Diabetes Mellitus At Rsi Jemursari Surabaya - Siti Robi’atus Sholiha; Yoga Ayom Pangestu; Abdul Manan; Ratna Yunita Sari; Himyatul Khoiroh (Sean Institute, 2023)
Diabetes mellitus (DM) is a chronic multisystem disease related to abnormal insulin production, impaired insulin utilization, or both. Prevention measures that can be taken to avoid DM include self-care management. This health promotion activity aims to educate the community, especially families affected by DM, about self-care management, with a total of 30 respondents. The health promotion method utilizes Power Point presentations (PPT) and leaflets, with pre-tests and post-tests conducted to assess the respondents' level of understanding. The research results show a significant difference in the respondents' knowledge of self care management before and after receiving education. The conclusion of this study is that providing health promotion to the community has a positive impact on the respondents' knowledge and quality of life, as well as on other members of the community.